Dati sulla urbanizzazione italiana: verso la terza generazione - Bernardino Romano; Francesco Zullo; Lorena Fiorini (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
In this current period, several attempts to classify the “made artificial” areas are occurring and tend to identify the categories on which match the amount of adverse environmental deterioration. Today the “institutional” database does not exist in appropriate scales that can provide an o cial fact, uniform and reliable, whereas there are a number of methodologies and information from scientific sources and pseudo such.